Orthopedic injury in 156 equids in Federal District, Midwestern Brazil - Moreira, Igor Louzada; Campebell, Rita Cássia; Teixeira-Neto, Antonio Raphael; Câmara, Antonio Carlos Lopes (Brazilian Journal of Veterinary Medicine, 2019)
The present study aimed to establish the prevalence of orthopedic injuries and main clinical-epidemiological findings in equids referred to the Large Animal Veterinary Teaching Hospital of the Universidade de Brasília (HVET-UNB), during a 2-year period (March 2016 to February 2018). All equids records during the 2-year period were reviewed to select the orthopedic injury cases. Animal records were divided into two groups: traction animals and those participating in other equestrian activities. Definitive diagnosis, reached by means of physical evaluation and ancillary diagnostic (radiography and ultrasonography) methods, showed that 34% (156 cases) of the referred 438 equids, presented some sort of orthopedic disorders in the two-year period. Of these cases, 151 (96.8%) were horses, four (2.6%) mules, and one (0.6%) donkey. Ninety (58%) were traction horses and 66 (42%) participated in other equestrian activities, while 45.5% (71/156) were females and 54.5% (85/156), males. Forelimbs were the most affected (51.9% - 81/156), followed by hind limbs (41.1% - 64/156) and vertebral column disorders (7% - 11/156). Furthermore, 75% (117/156) presented some degree of lameness while 25% (39/156) had no pain or gait alterations. The three major orthopedic injuries were bone disorders (40.4% - 63/156), tendinopathies (25.6% - 40/156) and arthropathies (13.5% - 21/156) while the digital (9% - 14/156), muscle (6.4% - 10/156) and ligament (5.1% - 8/156) injuries were observed less frequently. Total mortality rate reached 32.7% (51/156), and fractures represented the major orthopedic disease leading to euthanasia (80.4% - 41/51). The high number of traction equids attended (90 animals - 58%) indicates the still frequent use of these animals in large urban centers. The high mortality rate in this category (50% - 45/90), representing 90.1% (45/51) of all deaths, reveals the need for developing public policies prohibiting horses from circulating in urban areas while also improving their welfare in the rural area. We reiterate the importance of retrospective studies for identifying risk factors, proposing management changes and creating policies to avoid animal suffering and financial losses.